A stretchable polyaniline composite hydrogel based on ink direct writing 3D printing and its preparation method and application

Through the composite of cellulose nanocrystalline CNC, polyvinyl alcohol PVA and polyaniline PANI, ink suitable for direct ink writing 3D printing is regulated, which solves the problem that conductive polymer hydrogels in the prior art are difficult to take into account both conductivity and flexibility, and achieves the preparation of stretchable hydrogels with high viscosity and excellent performance, which is suitable for the field of flexible electronics.

CN115093581BActive Publication Date: 2025-02-28JIANGNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210882673.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-02-28
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

The existing conductive polymer hydrogel system is difficult to meet the ink requirements for direct ink writing 3D printing, and it is difficult to take into account excellent conductivity and mechanical flexibility, which limits its application in the field of flexible electronics.

Method used

By combining cellulose nanocrystalline CNC, polyvinyl alcohol PVA and polyaniline PANI, printing inks with appropriate viscosity and rheology characteristics are regulated, and stretchable conductive polymer composite hydrogels with specific structures and excellent properties are prepared by water bath concentration, 3D printing and freeze-thaw cycle treatment.

Benefits of technology

The uniform dispersion and high viscosity of conductive polymer hydrogels are achieved, the rheology performance of ink and the flexibility and tensile strength of hydrogels are improved, and it is suitable for personalized preparation in the field of flexible electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115093581B_ABST
    Figure CN115093581B_ABST
Patent Text Reader

Abstract

The present invention discloses a stretchable polyaniline composite hydrogel based on ink direct writing 3D printing and its preparation method and application, which belongs to the field of flexible electronics and wearable devices. The preparation method of the polyaniline composite ink for ink direct writing 3D printing of the present invention comprises the following steps: (1) dissolving cellulose nanocrystals CNC in a phytic acid PA aqueous solution, adding polyvinyl alcohol PVA solution and aniline monomer, adding ammonium persulfate APS after mixing, and performing an in-situ polymerization reaction; (2) evaporating the product after polymerization in step (1) to remove 15-25wt% of water. The composite hydrogel material prepared by the ink 3D printing of the present invention has a uniformly and continuously distributed conductive cross-linked network and a high-precision flexible structure, and can be widely used in the personalized preparation of flexible sensor device materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a stretchable polyaniline composite hydrogel based on ink direct writing 3D printing and a preparation method and application thereof, belonging to the field of flexible electronics and sensing materials. Background Art

[0002] In recent years, long-term stable wearable electronic devices have played an irreplaceable role in personal health monitoring and human-computer interaction. In order to improve the compatibility of wearable electronic devices with human skin and improve wearing comfort, it is crucial to develop hydrogel materials with high conductivity and good flexibility. Conductive polymer hydrogels are potential new materials for the development of a new generation of flexible wearable devices because they have both the electrochemical properties of conductive polymers and the flexibility and biocompatibility of hydrogels.

[0003] At present, the mainstream methods for preparing conductive polymer hydrogels include: (1) in situ polymerization of conductive polymers in a polymer gel system to construct a conductive polymer composite hydrogel with a double network structure; (2) during the polymerization of conductive polymer monomers, a small molecule crosslinking agent is added to promote the self-crosslinking of the generated conductive polymer to prepare a conductive polymer hydrogel. The conductive polymer hydrogels prepared by the above methods have the following problems: (1) The conductive polymers in the double network composite hydrogel prepared by the in situ polymerization method are prone to agglomeration, and it is difficult to obtain a uniformly dispersed three-dimensional conductive polymer network structure; (2) At present, the preparation of conductive polymer hydrogels is mostly through "sol-gel" mold molding, which is difficult to meet the needs of customized preparation, limiting its application in personalized wearable electronic devices.

[0004] 3D printing, also known as additive manufacturing, is a technology that achieves rapid prototyping by printing layer by layer. It has been widely used in the manufacture of functional equipment in many fields, such as biomedicine, electronics, engineering composites, microfluidics and energy storage systems. Direct ink writing (DIW) can obtain complex structures with high precision by designing layer by layer with less material. It is simple to operate and low in cost. It has been applied to many materials, including bio-inks, hydrogels and conductive inks.

[0005] The preparation of ink with certain rheological properties is an important prerequisite for the preparation of conductive polymer hydrogel by DIW. The ink required for DIW must be a non-Newtonian fluid with appropriate viscosity and shear thinning properties. The ink needs to have a large viscosity when there is no external force and presents a gel state, that is, its storage modulus needs to be greater than the loss modulus; when extruded through the extrusion needle, the ink is subjected to shear force, and its viscosity is significantly reduced, showing shear thinning characteristics; at this time, the loss modulus of the ink is higher than the storage modulus, showing a liquid-like state and can be extruded smoothly; after extrusion, the internal structure of the ink is restored and presents a gel state again, that is, the storage modulus is higher than the loss modulus, ensuring the good formability of the extruded structure.

[0006] Polyaniline (PANI) is a highly-regarded conductive polymer due to its superior environmental stability and biocompatibility. However, the molecular chain of polyaniline is relatively rigid, has high cohesive energy, is easy to aggregate, and is only soluble in a very small number of solvents, making it difficult to print by solution processing. In order to achieve solution processing of polyaniline, studies have found that N-methylpyrrolidone (NMP) can be used as a good solvent for PANI to prepare PANI ink. However, due to the solubility of PANI, the concentration of PANI in the ink is limited; in addition, NMP, as a toxic reagent, also limits its wide application.

[0007] Another study reported that the stable dispersion of polyaniline can be achieved by using small molecules of citric acid to prepare printing ink, but the viscosity of the printing ink is low and cannot meet the needs of DIW printing.

[0008] Therefore, how to obtain a printable ink with suitable viscosity and shear-thinning properties, and prepare a conductive polymer hydrogel with good conductive properties and mechanical flexibility is a problem that needs to be solved urgently. Summary of the invention

[0009] [Technical issues]

[0010] At present, the agglomeration phenomenon of the conductive polymer polyaniline is quite serious, and there are few environmentally friendly solvents that can disperse polyaniline. The existing conductive polymer hydrogel system is difficult to meet the requirements of DIW printing for inks, and the prepared hydrogel is difficult to balance excellent conductive properties and mechanical flexibility, which limits its application in the field of flexible electronics.

[0011] [Technical solution]

[0012] In order to solve the problems existing in the above prior art, the present invention provides a non-covalently cross-linked polyaniline composite ink suitable for ink direct writing 3D printing, and combines the ink direct writing 3D printing technology to prepare a 3D printable stretchable polyaniline composite hydrogel. The present invention adjusts the printing ink with suitable viscosity and rheological properties by compounding cellulose nanocrystals CNC, polyvinyl alcohol PVA and PANI, and prepares a stretchable conductive polymer composite hydrogel with a specific structure and excellent performance by water bath concentration, 3D printing and freeze-thaw cycle treatment.

[0013] The present invention uses CNC as a dispersant for PANI. On the one hand, it can effectively improve the agglomeration problem of PANI particles and make the printing ink evenly dispersed; on the other hand, since abundant hydrogen bonding can be formed between CNC and PVA, it is used as a rheological regulator for the composite hydrogel system, which can effectively increase the viscosity of the ink and improve the rheological properties of the ink; at the same time, since PVA can undergo a sol-gel transition and form a microcrystalline region after freezing at low temperatures, the flexibility of the composite hydrogel can be significantly improved, so that it has high tensile strength after freeze-thaw cycles. The present invention uses a high-temperature water bath to concentrate the ink, further increase the viscosity, and enhance the formability of the ink. The present invention uses a boric acid solution as a cross-linking accelerator for the hydrogel, so that it can further increase the degree of cross-linking after gelation at low temperatures, and further increase the tensile strength of the hydrogel by freeze-thaw cycles.

[0014] The first object of the present invention is to provide a method for preparing a polyaniline composite ink for ink direct writing 3D printing, the method comprising the following steps:

[0015] (1) dissolving cellulose nanocrystals CNC in phytic acid PA aqueous solution, adding polyvinyl alcohol PVA solution and aniline monomer, and then adding ammonium persulfate APS to carry out in-situ polymerization reaction;

[0016] (2) Evaporating the product after the polymerization reaction in step (1) to remove 15-25 wt % of water to obtain the product.

[0017] In one embodiment of the present invention, the temperature of the in-situ polymerization reaction in step (1) is 4-6°C.

[0018] In one embodiment of the present invention, the evaporation in step (2) is carried out in a water bath at 70-80°C.

[0019] In one embodiment of the present invention, in step (1), the molar ratio of the aniline monomer, PA and APS is 1-2:1-3:1-2; and the concentration of the phytic acid PA aqueous solution is 0.05-1 mol / L.

[0020] In one embodiment of the present invention, the molar ratio of the aniline monomer, PA and APS in step (1) is 1:1:1.

[0021] In one embodiment of the present invention, the CNC in step (1) is commercial cellulose nanocrystals prepared by sulfuric acid hydrolysis.

[0022] In one embodiment of the present invention, the molecular weight of the polyvinyl alcohol (PVA) in step (1) is 146,000 to 186,000, and the alcoholysis degree is >99%.

[0023] In one embodiment of the present invention, the PVA solution in step (1) is a PVA aqueous solution with a mass concentration of 10-15%.

[0024] In one embodiment of the present invention, the mass ratio of CNC to PVA in step (1) is 2:1 to 1:2.

[0025] In one embodiment of the present invention, the mass ratio of CNC to PVA in step (1) is 1:1.

[0026] In one embodiment of the present invention, the mixing process in step (1) is specifically as follows: first, CNC is added to the PA solution, and mixed evenly by magnetic stirring for 90 minutes to 150 minutes; then, the PVA solution is added, and mixed evenly by magnetic stirring for 20 minutes to 40 minutes; then, aniline monomer is added, and mixed evenly by magnetic stirring for 10 minutes to 20 minutes.

[0027] The second object of the present invention is to provide a polyaniline composite ink prepared by the above method.

[0028] The third object of the present invention is to provide a method for preparing a polyaniline composite hydrogel material, the preparation method comprising the following steps:

[0029] (1) transferring the polyaniline composite ink obtained above into a barrel and performing 3D printing to obtain a composite hydrogel with a pre-designed structure;

[0030] (2) freezing the composite hydrogel obtained in step (1) at -40 to -60°C to gel the PVA;

[0031] (3) immersing the composite hydrogel frozen in step (2) in a boric acid solution for further cross-linking;

[0032] (4) Repeat steps (2) and (3) for 3 to 5 cycles, rinse, and freeze overnight in a refrigerator to obtain a polyaniline composite hydrogel material.

[0033] In one embodiment of the present invention, the volume of the barrel in step (1) is 5 mL to 10 mL.

[0034] In one embodiment of the present invention, centrifugation is required to remove bubbles before 3D printing in step (1), and the centrifugation speed is 2000 rpm to 4000 rpm and the time is 3 min to 10 min.

[0035] In one embodiment of the present invention, the air pressure of the 3D printing in step (1) is 100 kPa to 500 kPa, and the printing speed is 4 mm s -1 ~10mm s -1 The needle diameter is 0.06mm~1.5mm.

[0036] In one embodiment of the present invention, the pre-designed structure in step (1) includes any one of a negative Poisson's ratio structure, an interpenetrating grid structure or an interdigitated electrode structure.

[0037] In one embodiment of the present invention, the freezing time in step (2) is 20 min to 50 min.

[0038] In one embodiment of the present invention, the concentration of the boric acid solution in step (3) is 0.5 mol / L to 0.9 mol / L, and the soaking time is 5 min to 20 min.

[0039] The fourth object of the present invention is to provide a polyaniline composite hydrogel material prepared by the above-mentioned preparation method.

[0040] The fifth object of the present invention is to provide an application of the above-mentioned polyaniline composite hydrogel material in the field of flexible electronics.

[0041] In one embodiment of the present invention, the flexible electronics include a flexible stretchable pressure sensor or a flexible electrode of a stretchable supercapacitor.

[0042] The sixth object of the present invention is to provide a flexible electronic device comprising the above-mentioned polyaniline composite hydrogel material.

[0043] In the present invention, polyvinyl alcohol is used as the flexible skeleton of the composite hydrogel system. The addition of its flexible macromolecular chain can significantly improve the flexibility of the composite hydrogel, and at the same time can increase the viscosity of the ink and improve the rheological properties of the ink; based on the electrostatic interaction between the negatively charged carboxylate on CNC and the positively charged polyaniline, and the hydrogen bonding between its carboxyl group and the PVA chain, a reversible non-covalent cross-linked network can be constructed in the ink to meet the "gel-sol-gel" transformation of the ink during 3D printing, thereby obtaining a printable ink. By utilizing the frozen cross-linking characteristics of PVA, the ink is subjected to low-temperature freezing molding after 3D printing to obtain a stretchable hydrogel with a strong cross-linked network, and then treated with boric acid immersion to further improve the mechanical properties of the composite hydrogel.

[0044] Beneficial effects of the present invention:

[0045] (1) The preparation method of the present invention is simple to operate, does not require high temperature and high pressure during the preparation process, takes a short time, and does not generate toxic and hazardous waste, thus meeting environmental protection requirements and being conducive to application and promotion.

[0046] (2) The present invention uses CNC as a viscosity regulator and a dispersant for PANI, and utilizes the multiple hydrogen bonds between molecular chains to achieve good dispersion of the conductive polymer; PVA is used as a viscosity regulator to make the printing ink meet the DIW printing requirements while giving the hydrogel good mechanical toughness, making it suitable for the field of flexible electronics.

[0047] (3) The ink direct writing printing technology adopted in the present invention can well achieve uniform deposition and high-precision regulation of composite hydrogels. By stacking layers, stretchable polyaniline composite hydrogel patterns with various structures or three-dimensional structures with negative Poisson's ratios are prepared, which can be used for the personalized preparation of flexible sensor materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a physical picture of the polyaniline composite hydrogel with a grid structure prepared in Example 1 of the present invention;

[0049] Figure 2 This is a physical picture of the stretched polyaniline composite hydrogel with a grid structure prepared in Example 1 of the present invention;

[0050] Figure 3 The graphs are rheological properties of the composite inks prepared in Examples 1, 2 and 3 of the present invention; wherein (a) is a graph showing the relationship between viscosity and shear rate; and (b) is a graph showing the relationship between modulus and oscillation strain.

[0051] Figure 4 Scanning electron microscope (SEM) images of the composite inks prepared in Example 1 (a), Example 4 (b), Example 5 (c) and Comparative Example 2 (d) of the present invention;

[0052] Figure 5 Graphs showing stress-strain curves of the polyaniline composite hydrogels prepared in Example 1 and Comparative Example 1 of the present invention;

[0053] Figure 6 Optical images of the polyaniline composite inks prepared in Example 1 and Comparative Example 2 of the present invention; (a) is an image of the two inks when the glass slide is placed flat; (b) is an image of the two inks when the glass slide is placed at an angle. DETAILED DESCRIPTION

[0054] The present invention is further described below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0055] The fiber nanocrystals CNC are commercial cellulose nanocrystals, prepared by sulfuric acid hydrolysis, with a length of about 200 nm and a diameter of about 10 nm, purchased from Shansi Technology; polyvinyl alcohol PVA, with a molecular weight of 146000-186000 and a degree of alcoholysis >99%.

[0056] Example 1

[0057] A method for preparing a stretchable polyaniline composite hydrogel based on ink direct writing 3D printing specifically comprises the following steps:

[0058] (1) Dissolve 0.707g (0.05mol / L) phytic acid (PA) in 5g ultrapure water, add 0.75g CNC (5%), and stir magnetically for 1.5h; then add 7.5g heated 10wt% PVA solution (the mass ratio of PVA to CNC is 1:1) (preparation of 10wt% PVA solution: prepared by stirring and dissolving in an 80℃ water bath for 8h), and mix evenly by magnetic stirring for 30min; then add 0.07g aniline monomer (0.05mol / L) and stir for 10min; slowly drip the prepared APS solution (dissolve 0.171g APS (0.05mol / L) in 1g ultrapure water, and completely dissolve it by ultrasonication for 20s) into the solution in the cup under rapid stirring, continue stirring for 10min, and then place in a 4℃ refrigerator for in-situ polymerization for 24h;

[0059] (2) After the polymerization is completed, the mixture is stirred in a 75°C water bath to evaporate and remove 20 wt% of the water to obtain a uniform printable ink; after the ink is cooled to room temperature, it is transferred to a 5 mL cylinder and centrifuged to remove bubbles at a centrifugal speed of 3500 rpm for 5 min;

[0060] (3) A needle with an inner diameter of 0.21 mm was installed at the lower end of the barrel, and the top was connected to the 3D printer. The pre-designed 3D printing model was imported to generate the printing path. The air compressor provided power, and the printing air pressure was controlled to 150 kPa and the printing speed to 6 mm s. -1 , completing the extrusion printing of the composite ink to obtain a composite hydrogel with a pre-designed structure;

[0061] (4) The printed hydrogel was placed in a culture dish and frozen in a low-temperature reaction bath at -50°C for 30 minutes; then taken out and soaked in a 0.9 mol / L boric acid solution for 10 minutes, and then placed in a low-temperature reaction bath and frozen for 10 minutes. This cycle was repeated three times. Finally, the boric acid on the surface was rinsed off with ultrapure water and the product was placed in the lower layer of a refrigerator at -20°C and frozen overnight to obtain the final polyaniline composite hydrogel, which was recorded as PPC-1.

[0062] Example 2

[0063] The mass ratio of PVA to CNC in Example 1 was changed to 2:1 (keeping the total mass of CNC and PVA unchanged), and the rest was the same as Example 1. The final composite hydrogel was recorded as PPC-2.

[0064] Example 3

[0065] The mass ratio of PVA to CNC in Example 1 was changed to 1:2 (keeping the total mass of CNC and PVA unchanged), and the rest was the same as Example 1. The final composite hydrogel was recorded as PPC-3.

[0066] Example 4

[0067] The concentration of the aniline monomer in Example 1 was changed to 0.02 mol / L, and the rest was the same as in Example 1. The composite hydrogel finally obtained was recorded as PPC-4.

[0068] Example 5

[0069] The concentration of the aniline monomer in Example 1 was changed to 0.2 mol / L, and the rest was the same as in Example 1. The composite hydrogel finally obtained was recorded as PPC-5.

[0070] Comparative Example 1

[0071] The freeze-thaw cycle operation in step (4) of Example 1 was omitted, and the remaining steps were the same as in Example 1; the printed hydrogel was directly frozen in a low-temperature reaction bath at -50°C for 1.5 h, and then placed in the lower layer of a refrigerator at -20°C for freezing overnight, and finally a composite hydrogel was obtained, which was recorded as PPC-6.

[0072] Comparative Example 2

[0073] The CNC in Example 1 was omitted, and the remaining steps were the same as those in Example 1. The composite hydrogel finally obtained was recorded as PPC-7.

[0074] The performance tests were performed on the composite hydrogels PPC-1 to PPC-7 prepared in Examples 1 to 5 and Comparative Examples 1 to 2, respectively.

[0075] The test results are as attached Figures 1 to 6 as shown; Figure 1 As shown: the composite ink prepared in Example 1 of the present invention has good formability and can be printed to prepare a polyaniline composite hydrogel with a 3D structure.

[0076] like Figure 2 As shown: the polyaniline composite hydrogel prepared in Example 1 has good stretchability and can still maintain shape continuity without breaking at 150% strain.

[0077] like Figure 3 As shown: the polyaniline composite inks of different CNC / PVA mass ratios in Examples 1 to 3 of the present invention all have good rheological properties. As shown in Figure a, the composite inks all have obvious shear thinning behavior, which can ensure smooth extrusion of the inks; as shown in Figure b, the prepared composite inks all have gel points, that is, there is an obvious "sol-gel" transition process, which proves that they have good fluidity during extrusion and good formability after extrusion.

[0078] from Figure 3 It can be seen that with the increase of CNC ratio, the viscosity and modulus of the composite ink increase accordingly (and are within the printable range). This is because the increase in the solid content of the system makes the contact between the polymers closer, the intermolecular force stronger, and the chain entanglement increases.

[0079] like Figure 4 As shown: the CNC component added in the present invention can play a good role in dispersing polyaniline. As shown in Figure a (Example 1), the internal structure of the composite hydrogel is relatively uniform, without obvious agglomerated particles; while in Figure d (Comparative Example 2), obvious larger polyaniline aggregates can be observed, proving that the internal dispersion of the ink without adding CNC is uneven and is not suitable for DIW printing; Figures a, b (Example 4), and c (Example 5) prove that the prepared polyaniline composite inks with different aniline concentrations can all disperse polyaniline well and can be extruded evenly and smoothly during the printing process. This is because there is an electrostatic interaction between the negatively charged carboxylate groups on CNC and the positively charged polyaniline, which enables polyaniline to be evenly dispersed in the network formed by CNC and PVA, thereby obtaining a more uniform printing ink.

[0080] like Figure 5 As shown in the figure, the mechanical strength of the polyaniline composite hydrogel prepared in the present invention is significantly improved after freeze-thaw cycle treatment. Figure 5 It can be seen that PPC-1 has higher tensile strength and modulus than PPC-6. This is because the boric acid immersion and freeze-thaw cycle treatment increase the cross-linking degree of the three-dimensional network structure inside the hydrogel, thus showing higher modulus and strength during the stretching process.

[0081] like Figure 6 As shown in the figure: the CNC component added in the present invention can provide viscosity and formability. As shown in Figure a, the PPC-7 ink in Comparative Example 2 without adding CNC has no formability and is in a very thin state, while the PPC-1 ink containing CNC has good formability; as shown in Figure b, on the inclined glass slide, the PPC-1 ink can still maintain its original shape without flowing, but the PPC-7 ink has a clear downward flow behavior.

[0082] Figure 3 and Figure 6 Together, it is proved that the addition of CNC makes the composite ink have good rheological properties and printability. This is because there is an electrostatic interaction between the negatively charged carboxylate groups on CNC and the positively charged polyaniline. At the same time, since abundant hydrogen bonds can be formed between CNC and PVA, the rheological properties of the composite hydrogel system can be adjusted, the viscosity of the ink can be effectively improved, and the ink has good formability and printing performance.

[0083] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a polyaniline composite hydrogel material, characterized in that: The preparation method comprises the following steps: (1) Transferring the polyaniline composite ink into a barrel and performing 3D printing to obtain a composite hydrogel with a pre-designed structure; (2) freezing the composite hydrogel obtained in step (1) at -40 to -60°C to gel the PVA; (3) immersing the composite hydrogel frozen in step (2) in a boric acid solution for further cross-linking; (4) Repeat steps (2) and (3) for 3 to 5 cycles, rinse, and freeze overnight in a refrigerator to obtain a polyaniline composite hydrogel material; The preparation method of the polyaniline composite ink comprises the following steps: 1) Dissolve cellulose nanocrystals CNC in phytic acid PA aqueous solution, add polyvinyl alcohol PVA solution and aniline monomer, mix and add ammonium persulfate APS to carry out in-situ polymerization reaction; The mass ratio of CNC to PVA is 2:1-1:2; the molar ratio of aniline monomer, PA and APS is 1-2:1-3:1-2; the concentration of PA aqueous solution is 0.05-1 mol / L; 2) Evaporating the product after the polymerization reaction in step 1) to remove 15-25 wt% of water to obtain the product.

2. The method for preparing the polyaniline composite hydrogel material according to claim 1, characterized in that: The air pressure of the 3D printing in step (1) is 100 kPa~500 kPa, and the printing speed is 4 mm s -1 ~10 mm s -1 , the needle diameter is 0.06mm~1.5mm.

3. The method for preparing the polyaniline composite hydrogel material according to claim 1, characterized in that: The concentration of the boric acid solution in step (3) is 0.5 mol / L to 0.9 mol / L, and the soaking time is 5 min to 20 min.

4. The polyaniline composite hydrogel material prepared by the method for preparing the polyaniline composite hydrogel material according to any one of claims 1 to 3.

5. Application of the polyaniline composite hydrogel material according to claim 4 in the field of flexible electronics.

6. A flexible electronic device comprising the polyaniline composite hydrogel material according to claim 4.

Citation Information

Patent Citations

  • Preparation method of aqueous polyaniline conductive printing ink

    CN105936770A

  • Ink direct writing 3D printing PEDOT: PSS composite hydrogel and preparation method thereof

    CN114316685A